DISTRIBUTION OF RABBITS’ PARASITOSIS IN PRIVATE ECONOMIES OF POLTAVA REGION - Клименко, О. С. (Scientific Progress & Innovations, 2015)
The analysis of literary data and own researches testify about considerable distribution of rabbits’ Parasitosis in the economies of different patterns of ownership in the most world countries. Almost general distribution of Psoroptosis, Eimeriosis and Passalurosis are set by laboratory researches of material from the rabbits of private economies of twelve districts in Poltava region. Extensivity of Psoroptes invasion presents 37,68 %, Eimeria – 47,69 %, Passalurus – 21,26 %, although in separate economies the indexes of defeat are 100 %. Obtained data testify the necessity of development and introduction of measures of fight against Parasitosis of rabbits in private economies.